[PP.08.06] IS THE DEVELOPMENT OF TELEMEDICINE IN HYPERTENSION A DIGITAL IMMIGRANT ISSUE ?. (September 2016) - Lopez-Sublet, M.; Baguet, J.-P.; Courand, P.-Y.; Bally, S.; Krummel, T.; Dimitrov, Y.; Brucker, M.; Regnier-Le-Coz, S.; Dourmap, C.; Mourad, J.-J.; Steichen, O.; Ott, J.; et al.
Abstract : Objective: Telemedicine refers to the use of medical information exchanged from one site to another via electronic communication and the role in the management arterial hypertension should strive against uncontrolled patients. Nowadays, patients easily e-transfer their results of home blood pressure measurement (HBPM) and practitioners receive and assess these HBPM results. Young generations, grown with the Internet, have been labelled "digital natives" (born after 1985) in comparison with older generations, labelled "digital immigrants", who need to learn e-technology. Thus, we aimed to collect data on technical equipment of physicians and patients, on their expectations of use about this way of relationship. Design and method: 116 physicians, hypertension specialists (36 ± 9 y, 50.8% men), mostly hospital practitioners (84.5%) and 322 hypertensive outpatients (61 ± 14.6 y, 60.4% men, SBP/DBP average 143 ± 19/82 ± 13 mmHg, 31.8% with diabetes) completed a self-administered questionnaire. Results: The prevalence of technical equipment in both groups is summarized in Table 1. Figure. No caption available. 68.2% of patients had an HBPM device (51.6% upper arm). From the 69/98 diabetic' patients used a blood glucose meter. 41% of patients vs 66% of physicians believed that telemedicine could improve the control of hypertension; 25% of patients vs 22% physicians thought that consultations' frequency could be lightened. 18% of physicians thought that HBPM would fight inertia. 75% of patients vs 84% of physicians would agree for HBPM data being transferred to a non- medical staff. Whilst 89.5% of physicians were supporting the development of telemedicine in their daily practice, 99% of them found many "limits" to this method: budget (49%), difficulties in accessing informatics tools (38%), medical reluctance (35%), lack of legal frame (34%), confidentiality (33%), absence of direct benefit (21%). Conclusions: Although our population has no daily access to the telemedicine, today technical equipment is no longer an obstacle. The majority of patients and medical practitioners agree with e-transfer of HBPM data. However physicians highlight various obstacles to its expansion: financial limits, medical reluctance and lack of legal frame. Telemedicine might take off when the natives will outnumber immigrants. Meanwhile, physicians have a key-role to lead the patients in their e-education.